Discovery of potent and selective Bcl-2 inhibitors with acyl sulfonamide skeleton. (1st October 2021) - Wang, Bin; Feng, Weiwei; Wang, Jinan; Dong, Yuanzhen; Liu, Yanlong; Yao, Yiyan; Zhang, Jianqing; Shi, Wei; Liu, Limin; Zhang, Hongying; He, Xiangyi; Chang, Xiayun; et al.
Graphical abstract: Highlights: Bcl-2 inhibitors with acyl sulfonamide skeleton were synthesized and evaluated. 24g displayed equal inhibition activity against RS4;11 compared to ABT-199. Improved selectivity for Bcl-2/Bcl-xL of 24g resulted in reduced platelet toxicity. In vitro and in vivo PK properties of 24g had a significantly improved profiles. Abstract: The antiapoptotic protein B-cell lymphoma 2 (Bcl-2), overexpressed in many tumor cells, is an attractive target for potential small molecule anticancer drug discovery. Herein, a series of novel derivatives with acyl sulfonamide skeleton was designed, synthesized, and evaluated as Bcl-2 inhibitors by means of bioisosteric replacement. Among them, compound 24g demonstrated equal efficient inhibition activity against RS4;11 cell line compared to positive control ABT-199. Moreover, it showed improved selectivity for Bcl-2/Bcl-xL inhibitory effects, the result of which was consistent with platelet toxicity studies. In vitro and in vivo pharmacokinetic properties of compound 24g had a significantly improved profiles. Taken together, those results suggested it as a promising candidate for development of novel therapeutics targeting Bcl-2 in cancer.